Miscommunication in the institutional context of the broadcast news interview : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Psychology at Massey University, Palmerston North, New Zealand - Hignett, Robert Michael (Massey University, 2004)
This study examined the pattern and relative success of linguistic interaction in the Broadcast News Interview (BNI). BNI is modelled as a genre of institutional communication. The psychological and functional characteristics of the BNI were examined from the viewpoint of how communicative conventions that normally regulate interview performance may, at times, impede effective communication. The BNI is intended to transfer information from an expert witness to an interested, though relatively uninformed audience. The interviewer is supposed to act as both conduit and catalyst. Pragmatic properties of the interlocutors' speech as they orient themselves towards the context of the conversation was analysed in order to reveal the manner in which prior assumptions or beliefs may lead to faulty inferences. The notion of miscommunication is used to describe and explain the faults associated with processes of representing the illocutionary force of an utterance, rather than deficiencies in pronunciation or auditory sensation and perception. Opting for a qualitative analysis, an attempt was made to ground explanations in relevant theoretical models of interpersonal communication and communication failure. Results indicate that the conventions that distinguish the BNI from more mundane types of interaction impede successful communication. The study highlights that participants who wish to attain their communicative goal must be more aware of the functional procedures of the BNI and anticipate impediments to successful communication.
Keywords: Miscommunication; Interviewing; Broadcast journalism